The taming of the shrew - Shakespeare, William, 1564-1616; Bloom, Harold (Shakespeare, William, 1564-1616. Works. 2003., 2005)
In one of Shakespeares bawdier comedies, contemporary audiences still take great pleasure in the rapid-fire verbal battles between the shrewish Katharina and the canny Petruchio, determined to subdue Katharinas legendary temper and win her dowry.